Surface Reconstruction Regulation of Co 3 N Through Heterostructure Engineering Toward Efficient Oxygen Evolution Reaction - Zeng, Ye; Zheng, Jiaxian; Zhang, Heru; Yao, Fen; Deng, Dingrong; Wu, Qihui; Makgwane, Peter R.; Liang, Hanfeng (Small (Weinheim an der Bergstrasse, Germany), 2024)
Oxygen evolution reaction (OER) electrocatalysts generally experience structural and electronic modifications during electrocatalysis. This phenomenon, referred to as surface reconstruction, results in the formation of catalytically active species that act as real OER sites. Controlling surface reconstruction therefore is vital for enhancing the OER performance of electrocatalysts. In this study, a new approach is introduced of heterostructure engineering to facilitate the surface reconstruction of target catalysts. Using MnCo carbonate hydroxide (MnCo─CH)@Co 3 N as a demonstration, it is discovered that the surface reconstruction occurs more readily and rapidly on MnCo─CH@Co 3 N than on Co 3 N. More interestingly, during the reconstruction process, Mn species migrate to the surface, enabling the in situ formation of highly active Mn‐doped CoOOH. Consequently, the MnCo─CH@Co 3 N catalyst after reconstruction exhibits a low overpotential of 257 mV at 10 mA cm −2 , compared to 379 mV of individual Co 3 N. This work offers fresh perspectives on understanding the enhanced OER performance of heterostructure electrocatalysts and the role of heterostructure in promoting surface reconstruction.